Flying maggots: a smart logistic solution to an enduring medical challenge. Issue 2 (7th August 2017) - Tatham, Peter; Stadler, Frank; Murray, Abigail; Shaban, Ramon Z.
Abstract : Purpose: Whilst there is a growing body of research which discusses the use of remotely piloted aircraft systems (RPAS) (otherwise known as "drones") to transport medical supplies, almost all reported cases employ short range aircraft. The purpose of this paper is to consider the advantages and challenges inherent in the use of long endurance remotely piloted aircraft systems (LE-RPAS) aircraft to support the provision of medical supplies to remote locations – specifically "medical maggots" used in maggot debridement therapy (MDT) wound care. Design/methodology/approach: After introducing both MDT and the LE-RPAS technology, the paper first reports on the outcomes of a case study involving 11 semi-structured interviews with individuals who either have experience and expertise in the use of LE-RPAS or in the provision of healthcare to remote communities in Western Australia. The insights gained from this case study are then synthesised to assess the feasibility of LE-RPAS assisted delivery of medical maggots to those living in such geographically challenging locations. Findings: No insuperable challenges to the concept of using LE-RPAS to transport medical maggots were uncovered during this research – rather, those who contributed to the investigations from across the spectrum from operators to users, were highly supportive of the overall concept. Practical implications: The paper offers an assessment of the feasibility of the use of LE-RPAS to transport medical maggots. In doing so, it highlights a number of infrastructure and organisational challenges that would need to be overcome to operationalise this concept. Whilst the particular context of the paper relates to the provision of medical support to a remote location of a developed country, the core benefits and challenges that are exposed relate equally to the use of LE-RPAS in a post-disaster response. To this end, the paper offers a high-level route map to support the implementation of the concept. Social implications: The paper proposes a novel approach to the efficient and effective provision of medical care to remote Australian communities which, in particular, reduces the need to travel significant distances to obtain treatment. In doing so, it emphasises the importance in gaining acceptance of both the use of MDT and also the operation of RPAS noting that these have previously been employed in a military, as distinct from humanitarian, context. Originality/value: The paper demonstrates how the use of LE-RPAS to support remote communities offers the potential to deliver healthcare at reduced cost compared to conventional approaches. The paper also underlines the potential benefits of the use of MDT to address the growing wound burdens in remote communities. Finally, the paper expands on the existing discussion of the use of RPAS to include its capability to act as the delivery mechanism for medical maggots.